(untitled) (African Journal of Biomedical Research, 2023)
Rodents are one of the constraints of crop production in south western Nigeria. Some species have also been implicated as the vector of zoonotic diseases. In Nigeria, farmers usually contend with the problem of rodent damage and management. The present study was therefore aimed at harvesting the experiences of farmers about damage due to rodent and its management in the cereal crops farming system in Ife Central Local Government, Ile-Ife, South-West, Nigeria. Data were collected using questionnaires which were administered to 100 randomly selected farmers in the study area. The data collected were analysed using Statistical Package for Social Sciences (SPSS) version 20.0 and descriptive statistics (Frequency and percentages) were computed. The cereal crop identified to suffer rodent damage was maize - field (54.0%) and store (61.0%). Maturity stage was identified as the most susceptible stage to rodent damage in cereal crop production (38.0%). Inputs used for rodent management were obtained from Agrovets (48.0%) and local markets (43.0%). Most farmers (38.0%) usually start rodent management after noticing damage. Most frequently used rodent management method was rodenticides (44.0%). Most of the farmers (87.0%) were willing to cooperate for management of rodent. Majority of the farmers (83.0%) have enjoyed government support in rodent management in the past. Conclusively, rodent species usually attack maize crop both on the crop field and in the store. Rodenticides and environmental sanitation have been the commonly used rodent management methods